2020
DOI: 10.1111/jcpe.13347
|View full text |Cite
|
Sign up to set email alerts
|

Buccal bone thickness of maxillary anterior teeth: A systematic review and meta‐analysis

Abstract: As modern criteria for implant success have expanded to include parameters not only at the implant, peri-implant soft tissue and prosthesis levels, but also the patient's subjective evaluation, the planning and execution of implant rehabilitation in the anterior maxilla has become increasingly complex (Papaspyridakos, Chen, Singh, Weber, & Gallucci, 2012). In these cases, anterior implant treatment should satisfy the high aesthetic demands of the patient in order to obtain a result that best imitates the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 41 publications
6
36
4
1
Order By: Relevance
“…It was found that along the 6 mm of the alveolar crest, there are no meaningful differences in RW, BW and PW/LW. This finding contradicts most published data reporting a consistent increase in the RW [ 31 ] BW and PW/LW in the dentate maxilla and the mandible, when moving apically [ 31 , 37 , 39 , 56 , 57 ]. This happens probably since statistical comparisons were performed between consecutive depths along the ridge and not between intervals/ group of depths.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It was found that along the 6 mm of the alveolar crest, there are no meaningful differences in RW, BW and PW/LW. This finding contradicts most published data reporting a consistent increase in the RW [ 31 ] BW and PW/LW in the dentate maxilla and the mandible, when moving apically [ 31 , 37 , 39 , 56 , 57 ]. This happens probably since statistical comparisons were performed between consecutive depths along the ridge and not between intervals/ group of depths.…”
Section: Discussioncontrasting
confidence: 99%
“…Several factors contribute to this high heterogeneity, which are mostly connected to the study population selected in the included studies. Factors, such as possible anatomical difference between males and females [ 31 , 42 , 57 59 ], possible age effects (young vs. aged population), as in [ 31 , 38 , 57 ], or ethnic differences [ 29 ], were all found to effect alveolar ridge components, contributing to statistical heterogeneity. Moreover, no information was given in any of the included studies on the healing time following tooth extraction, which is a determinant factor influencing the extent of ridge resorption and the difference between RW in dentate and edentulous state [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 16 articles included, 4 were randomized clinical trials [ 4 , 6 , 13 , 14 ], 5 were prospective clinical trials [ 15 , 16 , 17 , 18 , 19 ], 4 were retrospective studies [ 2 , 7 , 20 , 21 ], and 3 were case series [ 8 , 22 , 23 ]. In addition, 6 articles compared the outcomes of conventional immediate dental implant placement versus such placement using the socket-shield technique [ 4 , 6 , 12 , 13 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, this location usually presents a narrow buccal cortical plate, which increases the risk of marginal bone resorption after tooth extraction [ 22 ]. Moreover, Tsigarida et al reported that most of the buccal bone walls in anterior maxillary teeth are narrower than 1 mm at the coronal third, and buccal bone walls wider than 2 mm were only measured in the middle third of canine and premolar teeth and in the apical third of every tooth [ 23 ]. However, the thickness of the marginal bone crest around teeth can remain stable due to the vascular supply from the periodontal vessels [ 24 ], although a thin marginal bone crest around dental implants can be reabsorbed, leading to the exposure of the rough surface of the dental implant [ 24 ] because the fasciculated bone of the internal portion of the alveolus is usually reabsorbed after tooth extraction without the adjacent periodontal tissues [ 24 ], leading to an unaesthetic effect due to the retraction of the buccal mucosa after buccal bone resorption [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…This area often shows a thin buccal bone plate (i.e., less than 1 mm), highly correlated with the loss of volume mentioned above (Tomasi et al, 2010;Tsigarida et al, 2020). In order to prevent this buccal hard tissue shrinkage, the use of bone substitute between the extraction socket buccal wall and the dental implant has been suggested in several studies (Araújo et al, 2015;Fickl et al, 2008).…”
Section: Introductionmentioning
confidence: 99%